2020
DOI: 10.5539/jas.v12n10p116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Juvenile Growth and Yield Relationship Among Dwarf Cashew Types in Ghana

Abstract: Cashew (Anacardium occidentale L.) is an important tropical cash crop cultivated in Ghana. It provides livelihood for about 200,000 people and contributes 6.1% to Ghana’s gross domestic product (GDP). Four Brazilian dwarf accessions were introduced to improve nut yield. Objectives of this study were to (1) assess the agronomic performance of the accessions across two contrasting ecologies, (2) determine environmental influence on juvenile growth, (3) determine the relationship between early vegetativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
4
6
1
Order By: Relevance
“…Adu et al (2013) observed a no significant genotype by environmental interaction for grain yield and other agronomic traits among extra early hybrids in Ghana, which is similar to findings observed in this study. However, Dadzie et al (2018) reported of significant genotype by environment interaction when he evaluated a larger number of hybrids including these same hybrids across three locations in two seasons in Ghana, which is in contrast with the findings of this work. Because this study involved only the topperforming hybrids identified by Dadzie et al (2018), it suggests that no significant differences existed among those top-performing hybrids identified by Dadzie et al (2018), even when evaluated in diverse ecologies as was done in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Adu et al (2013) observed a no significant genotype by environmental interaction for grain yield and other agronomic traits among extra early hybrids in Ghana, which is similar to findings observed in this study. However, Dadzie et al (2018) reported of significant genotype by environment interaction when he evaluated a larger number of hybrids including these same hybrids across three locations in two seasons in Ghana, which is in contrast with the findings of this work. Because this study involved only the topperforming hybrids identified by Dadzie et al (2018), it suggests that no significant differences existed among those top-performing hybrids identified by Dadzie et al (2018), even when evaluated in diverse ecologies as was done in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, GH11 (ENT-5 x TZ1-8), GH08 (MO826-12F x CML-343), GH05 (ENT-85 x CML-247), and GH09 (MO826-7F x CML-343) all recorded aflatoxin levels, which were below the 20 ppb threshold although under artificial inoculation. This observation compares with the findings from Dadzie et al (2018) who reported aflatoxin levels of 17.20 ppb, 21.74 ppb for ENT-5 x TZ1-8 and ENT-5 x CML-287, respectively, after inoculation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Broad sense heritability among traits ranged from moderate to very high estimates during the major season where adequate rains and less disease pressure was observed. However, significantly lower range of estimates were detected during the minor season (data not shown) confirming earlier reports by [17] who demonstrated significant environmental influence on heritability estimates in cashew. Moderate to high heritability estimates realized in this study, suggested that possible gains are achievable in hybrid maize development for high yields and aflatoxin accumulation resistance.…”
Section: Discussionsupporting
confidence: 90%